Postmodernist fiction - McHale, Brian (Routledge, 1987)
"This is one of the most lively and lucid studies of contemporary fiction around. Whether or not you agree with his provocative definition of the postmodern, McHale's argument is always engaging, bold and forceful"--Linda Hutcheon